Caspase-Independent Regulated Necrosis Pathways as Potential Targets in Cancer Management - Lou, Jianyao; Zhou, Yunxiang; Feng, Zengyu; Ma, Mindi; Yao, Yihan; Wang, Yali; Deng, Yongchuan; Wu, Yulian (Frontiers in Oncology, 2021)
Regulated necrosis is an emerging caspase-independent type of cell death. Recently, with increasing findings of regulated necrosis in the field of biochemistry and genetics, the underlying molecular mechanisms and signaling pathways of regulated necrosis are gradually understood. Nowadays, there are several modes of regulated necrosis that are tightly related to cancer initiation and development, including necroptosis, ferroptosis, parthanatos, pyroptosis, and so on. What’s more, accumulating evidence shows that various compounds can exhibit the anti-cancer effect via inducing regulated necrosis in cancer cells, which indicates that caspase-independent regulated necrosis pathways are potential targets in cancer management. In this review, we concentrate our efforts on the molecular mechanisms and signaling pathways of multiple modes of regulated necrosis; we also focus on their roles in tumorigenesis. Furthermore, this review explores how each of the regulated necrosis pathways could be therapeutically targeted.